KEBIJAKAN PEMERINTAH KOTA SURABAYA DALAM MEMANFAATKAN RUANG TERBUKA HIJAU KEBUN BIBIT BRATANG - Hidayati, Nurul (Jurnal Review Politik, 2015)
This study examines the policies of the Surabaya government in developing green-open spaces in the Bratang nurseries. Exploiting such green-open spaces becomes an answer to environmental problems, such as air and water pollution, faced by many urban cities like Surabaya. Although the area is still less managed and is disputed by the private parties against the Surabaya government, its ecological role is undoubtedly essential. The results of the research indicate that the implementation of the Surabaya government’s policies regarding park management in the form of open-green spaces in the Bratang nurseries is adequate.The area is now complemented with sufficient public facilities and it can be used as the place for educational purposes.